Influence of Motivation and Knowledge of Enterprise on Interest in Enterprise Students Grade XI, XII at SMK Arrahmaniyah Tajurhalang - Ayu Saidah; Ikhwan Hamdani; Syarifah Gustiawati (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2023)
Competition in the world of work is currently very tight, the absorption of labor in the business world and industry as well as the recruitment of civil servants is very limited and with a high level of competence. Seeing these conditions, the world of education must be able to play an active role in preparing educated human resources who are able to apply in social and creative life who are able to create jobs for themselves and others. This research was researched by Ayu Saidah with student number: 161104080038 at Ibn Khaldun University of Bogor. The purpose of this study was to determine the effect of entrepreneurial motivation and entrepreneurial knowledge on entrepreneurial interest in students of SMK Arrahmaniyah Tajurhalang. The research method used in this study is survey research, researchers will go directly to the object of research. Then the data collection instrument in this study using a questionnaire. The results showed that; The influence of Entrepreneurial Motivation and Entrepreneurship Knowledge has a significant value on Entrepreneurial Interest in students of SMK Arrahmaniyah. This is evidenced by the results of multiple linear regression which produces an Fcount value of 33,878 with a significance of 0.000. Then the result of the significance is 0.000 <0.05. Which means that there is a significant influence between the two independent variables, namely Entrepreneurial Motivation (X1) and Entrepreneurship Knowledge (X2) on Entrepreneurial Interest (Y). Individually the Entrepreneurial Motivation variable provides a coefficient value of 0.468 and Entrepreneurial Knowledge provides a coefficient value of 0.379 which means it has a positive value.